Accuracy of the fully integrated Insole3's estimates of spatiotemporal parameters during walking. (January 2023) - Ganguly, Abhiroop; Olmanson, Bjorn A.; Knowlton, Christopher B.; Wimmer, Markus A.; Ferrigno, Christopher
Highlights: The Insole3 is an accurate method for assessing cadence, cycle time, and stance time. Averaging multiple walking trials improves accuracy for speed and stride length. The Insole3 is a potential alternative to three-dimensional motion capture systems. Spatiotemporal data from the Insole3 can be used in clinical scenarios. Abstract: This study investigated the accuracy of the Insole3 wireless shoe device in estimating several clinically useful spatiotemporal parameters (STPs). Eleven subjects walked at slow (0.8–1.0 m/s) and moderate-paced (1.2–1.4 m/s) speeds. Data were simultaneously recorded using the Insole3 and an industry-standard, three-dimensional motion capture (MOCAP) system. An error analysis compared the resulting STP data from the two systems. The mean bias error (MBE) was generally lower for temporal variables, and somewhat higher, but acceptable, for spatial variables. The MBE for temporally-related cadence and cycle time were the lowest (less than ±0.45%), with 100% (110/110) of slow-paced walking trial values and 99.1% (109/110) of moderate-paced walking trial values within 5% of the MOCAP estimates. The MBE was highest for speed (3.23–4.91%) and stride length (3.68–4.63%), with between 52.7 and 69.1% of trial values falling within the 5% error range. Stance time and swing time ranged between -0.98 and 4.38% error for both walking conditions. The results of this study suggest that the Insole3 is a potential alternative to MOCAP for estimating several STPs, namely cadence, stance time, and cycle time, particularly for use outside of the laboratory setting. Graphical abstract: Image, graphical abstract